309 Understanding public perceptions of research study participation – A survey study - Jennifer McCormick; Jennifer M Poger; Shaweta Singla; Alyson Eggleston; Jennifer L Kraschnewski (Journal of Clinical and Translational Science)
Objectives/Goals: Research participants are not representative of our communities. To determine research perceptions, we are recruiting individuals who have and have not participated in studies. We aim to identify trends, capturing motivating factors, access barriers, and participants’ concerns to inform best practices to engage participants. Methods/Study Population: We developed a 25-item survey with a goal of engaging 500 individuals. Survey questions were developed based on published literature of research motivations and barriers, as well as focus groups conducted in our central Pennsylvania community. Survey questions consist of Likert-scale, multiple choice, and free text, with administration through REDCap. Potential survey participants will be recruited from the Penn State Volunteer Repository and through partnering clinical networks, including federally qualified health centers. We will also recruit individuals who have never participated in research to engage underrepresented groups via the Penn State Clinical and Translational Science Institute’s community partner network. Analyses will include Chi-squared tests and binomial logistic regression. Results/Anticipated Results: The primary dependent variable will be past participation in research, while the primary independent variables will be binary responses to questions relating to motivators and barriers to participation in research. Secondary analysis will stratify these comparisons by race or rurality with a subgroup analysis using the same methods as the primary analysis. Based on these analyses, we anticipate that those who have never participated in research will face greater and different barriers than those who have participated in research. We also anticipate that motivators will be similar between to the two groups. We anticipate finding differences in motivators and barriers among different races as well as differences when examining rurality versus non-rurality. Survey results will be available in January. Discussion/Significance of Impact: This will be one of the few studies in the literature focused on uncovering motivators and barriers to research participation. Understanding what motivates and prevents individuals from participating in research is one of the first steps to enhancing the research process so that people want, and are able, to participate in studies.